Diagnóstico situacional turístico de la parroquia Cangonamá en el cantón Paltas, provincia Loja - Espinosa Noboa, Paola Gisselle (2016)
In Ecuador who currently work in the tourist sector have conceived the importance of local management to achieve the exits from public or private initiatives consigned to integrate the community in the tourism development process. This factor is reflected in the generation of employment, and infrastructure improvement, incorporation of basic services, etc; becomes not only a great challenge for the administration but also an opportunity for the localities that have seen tourism as an economic alternative. At the same time in rural areas there is the inadequate management that has long been implicated for a long time, as evidenced by the poor utilization of tourist resources without taking into consideration their deterioration, before this problem, the world tourism organization proposed by the conversation of the tourism in an activity that has as main objective to balance economic, social and environmental in other words apply the sustainability of tourism through the correct timely planning of the destinations. Through the two polls in the place of study, we were able to see the absence of a diagnosis and tour several flaws that do not allow its development which is why raised achievable goals that will allow us to take advantage of the resources and establish strategies for moving forward. The overall objective of this work was; Identify alternatives of tourism development in the parish Cangonama Avocado of the canton of the province of Loja, through a tourist diagnosis; for this and ran three specific objectives: to characterize the current situation of tourism in the parish with its opportunities and limitations, determine the composition of the tourism supply and demand and design strategies for the development of tourism sector. This research involved methods such as facilitating scientific research with a logical sequence, the bibliographic providing all the conceptual referents, the analytical method for the decomposition of the placement of the features of the tourism system components and the synthetic sort and rebuild the entire decomposed. In addition it was essential the use of certain investigative techniques such as direct observation where it proceeded to develop an inventory of tourist sites in the parish Cangonama, using the methodology of the Ministry of Tourism and technical instruments of precision; the interview whose objective was to collect the necessary information of the study site, through the implementation of the recommended format in the manual for the diagnosis of Local Tourist Charter Ricaurte Quijano; for the analysis of demand were surveyed to the visitors of the parish Cangonama finally it should be emphasized that for designing strategies of tourism development was used the technical MARPP which consisted in a participatory workshop, where those involved participated in the design of a SWOT matrix and pointed out the possible programs and projects. The results are checked by using the establishment the base line that allow you to develop the three specific objectives; it succeeded in integrating the components of the tourism system gathering required information; determination of the offering that demonstrates the potential for tourism with seven sites identified in category I and II as are cross of cold water, Cerro Cango , exchange of images, Naum Briones, typical food, Fiestas of Healthy Municipios Strategy, feasts of the Virgin of the Assumption, as well as points to a minimum number of service providers; of tourism demand where they identified the profile of tourists; the design of strategies led to the creation of new programs and projects that generate A better quality of life for the actors and director indirect linked in the tourism activity. Culminating with the situational assessment tourist resort, considered one of the conclusions that the parish Cangonama has large natural tourist attractions and cultural that can attract several visits; in addition is characterized by being a sector agroecological and submit a climate suitable for health. It is as well as it is defined that the main weakness of the sector is the weak signals and valuation of the tourism resources where it is recommended to the relevant authorities to implement the preservation of the same.